Paraneoplastic pemphigus and Castleman's disease: a case report and a revision of the literature - Mariangela Irrera; Elena Bozzola; Antonello Cardoni; Rita DeVito; Andrea Diociaiuti; Maya El Hachem; Katia Girardi; Alessandra Marchesi; Alberto Villani (BMC, 2023)
Abstract Background In literature, a few reports described an association between paraneoplastic pemphigus (PNP) and Castelman's disease (CD), but no consensus have been proposed for the diagnostic-therapeutical approach. Aim of this study is to present a case report and explore the relationship between PNP and CD in pediatric patients, focusing on clinical manifestations, histopathological findings, treatment and outcome to find elements for an early diagnosis. Case presentation We present the clinical case of a 13 years old girl with a challenging diagnosis of PNP and CD who underwent therapy at first with Rituximab and then with Siltuximab, for the control of symptoms. Conclusions Reviewing literature, 20 clinical cases have been described in the pediatric age. Diagnosis may be challenging, requiring an average of 3 months (range from 3 weeks to 2 years). In all cases, the initial manifestations were mucocutaneous lesions, especially oral lesions with poor response to conventional treatment. Systemic symptoms may be present as well. Therapeutical approach is still discussed with no consensus. Almost all patients received corticosteroids with poor response. Other drugs including azathioprine, methotrexate, cyclosporine and monoclonal antibodies have been evaluated for the control of the disease. Further studies and experimental trials urge to define the diagnostic criteria and therapy protocol.